(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Argopecten circularis (Sowerby, 1835) fecunddity was estimated during spawnings of February-March 1989 and March-May 1990 in Bahía Concepción, Baja California sur, México. In general, the number of oocytes released during the spawning of Argopecten circularis were potentially related to shell height. The calculated average oocyte wet weight during the maturity period was 8.9033x10A-8 g. Spawning ocurred in individuals 44 to 77 mm in height. The highest fecundity occurred in bivalves 58 to 77 mm in height. Mean fecundity obtained for all heigts by regression analysis during spawning in February-march 1989 was 12, 102, 243 oocytes. In April- May of the same year, there were 17, 917, 006 oocytes, and during March-May 1990, 16, 938, 117 oocytes.